2023
DOI: 10.3390/polym15061513
|View full text |Cite
|
Sign up to set email alerts
|

Emission of Volatile Organic Compounds in Crumb Rubber Modified Bitumen and Its Inhibition by Using Montmorillonite Nanoclay

Abstract: Bitumen emits a large amount of volatile organic compounds (VOCs) during the production and construction of asphalt mixture, which can cause both environmental hazards and health risks. In this study, a setup was designed to collect the VOCs released by base and crumb rubber-modified bitumen (CRMB) binders and their composition was characterized by thermal desorption-gas chromatography-mass spectrometry (TD-GC-MS). Next, organic montmorillonite (Mt) nanoclay was added into CRMB binder and its inhibiting effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Rohayzi et al [ 17 ] reviewed polyphosphoric acid, Evotherm, mangosteen powder, trimethyl-quinoline and sulfur related to the additives that can improve the properties of rubberized asphalt. Liu et al [ 18 ] have found that montmorillonite (Mt) nano clay could act as an effective modifier by adding Mt nano clay to crumb rubber-modified bitumen binder.…”
Section: Introductionmentioning
confidence: 99%
“…Rohayzi et al [ 17 ] reviewed polyphosphoric acid, Evotherm, mangosteen powder, trimethyl-quinoline and sulfur related to the additives that can improve the properties of rubberized asphalt. Liu et al [ 18 ] have found that montmorillonite (Mt) nano clay could act as an effective modifier by adding Mt nano clay to crumb rubber-modified bitumen binder.…”
Section: Introductionmentioning
confidence: 99%
“…HiSorb-TD, as an emerging pre-treatment method for volatile substances, is usually combined with gas chromatography-mass spectrometry (GC-MS). At present, it has been applied in the detection of environmental air [ 21 , 22 ] and chemical material security [ 23 , 24 ], but not in food, especially in raw meat.…”
Section: Introductionmentioning
confidence: 99%